Eficiência de nematicidas biológicos e químicos no manejo de Meloidogyne enterolobii em goiabeira - Alves, Cíntia da Silva (2016)
Given that the decline of the guava tree is characterized as a complex disease caused by parasitism M. enterolobii, which predisposes the plant to root rot caused by the fungus Fusarium sp. Three experiments were carried out in vitro with the following ob